Molecular architecture of thin films fabricated via physical vapor deposition and containing a poly(azo)urethane - Alessio, Priscila [UNESP]; Leopoldo Constantino, Carlos Jose [UNESP]; Job, Aldo Eloizo [UNESP]; Aroca, Ricardo; Perez Gonzalez, Eduardo Rene [UNESP] (Amer Scientific Publishers, 2010)
Organic thin films are widely applied as transducers in devices whose performance is determined by the optical and electrical properties of the films. In this context, the molecular architecture of the thin films plays an important role. In this work we report the fabrication and characterization of a poly(azo)urethane synthesized fixing CO(2) in bis-epoxide followed by a copolymerization reaction with an azodiamine without using isocyanate. The poly(azo)urethane thin films were fabricated by physical vapor deposition (PVD) technique using vacuum thermal evaporation. The molecular architecture of the PVD films was investigated under control growth at nanometer level of thickness, as well as the surface morphology at micro and nanometer scales and the molecular organization. The thermal stability of the poly(azo)urethane molecules, which is a challenge in itself considering the thermal evaporation process, was followed by thermogravimetric analysis (TG) and also by both Fourier transform infrared absorption (FTIR) and ultraviolet-visible (UV-vis) absorption spectroscopies. The UV-vis absorption spectra showed a linear growth of the absorbance of the PVD films with the mass thickness measured by a quartz crystal balance. A random distribution of the poly(azo)urethane molecules in the PVD films was revealed by FTIR spectra. The film morphology was investigated at microscopic level combining chemical and topographical information through micro-Raman technique. At nanoscopic scale, the morphology was investigated by atomic force microscopy (AFM) for films fabricated using distinct evaporation rates. As a proof of principle (for potential applications), the film luminescence was measured over a wide range of temperature. Interestingly, an unusual increase of fluorescence intensity was observed at +150 degrees C after a monotonic decrease from -150 degrees C.
Keywords: Poly(azo)Urethane; CO(2) Fixation; PVD Thin Films; AFM; Micro-Raman